E-056 Association of Engorged Perforating Artery of Basilar Top with Non-aneurysmal Perimesencephalic Subarachnoid Hemorrhage. (29th July 2016) - Moon, B; Park, S; Jang, K; Jang, D
Abstract : Introduction: Perimesencephalic subarachnoid hemorrhage (PM-SAH) accounts for about 10% of all SAHs, and digital subtraction angiography (DSA) is mostly found to be normal in such patients. The purpose of this study is to investigate the relationship between counts and diameter of engorged perforating artery of basilar top and non-aneurysmal PM-SAH. Methods: DSA findings of all patients who underwent catheter angiography for evaluation of non-aneurysmal PM-SAH between May 2014 and March 2015 were reviewed. Patients with anterior circulation aneurysms were excluded. PM-SAH and control group were evaluated by DSA 3D reconstruction images. Perforating artery diameters were measured and were counted engorged artery. Non-aneurysmal PM-SAH were identified: (1) center of bleeding located immediately anterior and in contact with the brain stem in the prepontine, interpeduncular, or posterior suprasellar cistern; (2) blood limited to the prepontine, interpeduncular, suprasellar, crural, ambient, and/or quadrigeminal cisterns and/or cisterna magna; (3) no extension of blood into Sylvian or interhemispheric fissures; (4) intraventricular blood limited to incomplete filling of the fourth ventricle and occipital horns of the lateral ventricles (ie, consistent with reflux); (5) no intraparenchymal blood. Results: 4 patients with non-aneurysmal PM-SAH and control group with posterior circulation aneurysms or dissection were identified. In patients with non-aneurysmal PM-SAH, mean diameters and counts of perforating artery were 1.002 mm(min-max, 0.85–1.26) and 3.75 (min-max, 3–4). In control group, diameters and counts were 0.663 mm (min-max, 0.5–1.12) and 2.4 (min-max, 1–4). Conclusions: There is a relationship between PM-SAH and engorged perforating artery counts and diameters. In patients of PM-SAH, there were found increased counts and diameters of perforating artery of basilar top. Disclosures: B. Moon: None. S. Park: None. K. Jang: None. D. Jang: None.